The Curse of Sisyphus: Why democracy isn’t necessarily good for press freedom in Africa - Onyango-Obbo, Charles (Development, 2013)
The advent of plural politics in Africa was also accompanied by burgeoning press freedom. It was assumed that a free press would underpin the democratic gains and allow for multiple ideas to flourish. Yet the record seems to suggest that things are different. The press is increasingly under attack from governments on the one hand who seek to weaken its capacity to be an effective message bearer, and on the other, the press itself is also adapting to and effectively exploiting regional differences in order to maximize its own profits, perhaps at the expense of national unity.
Keywords: Media; Press freedom; Africa; Democracy; Political parties